PELAKSANAAN THALAQ SECARA FIQIH ISLAM DI KECAMATAN PULAU RAKYAT KABUPATEN ASAHAN (DI TINJAU DARI UU NO.1 TAHUN 1974 TENTANG PERKAWINAN) - ULUL AZMI UTAMI BUTAR-BUTAR (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1. Prof. H.M. Hasballah Thaib, MA, PhD2. Dr. Utary Maharany Barus, SH, Mhum3. Dr. Yefrizawati, SH, MHum Thalaq (divorce) is halal even though God the Almighty does like it. When a husband says the word, “thalaq” to his wife, although it is said in joking or emotionally, it is officially done. The people in Pulau Rakyat Sub-district who are Moslems in majority have some problems with the implementation of the Marriage Law even though Law No. 1/1974 has been practiced since three decades ago. However, the problem of thalaq is not stipulated in Law on Marriage and its violation still exists. The research problems are how about the regulation on thalaq in the Islamic fiqh, why the people in Pulau Rakyat Sub-district do not do thalaq according to Law No. 1/1974 on Marriage, and how about the perception of Law No. 1/1974 on thalaq in the Islamic fiqh.Keywords: Thalaq, Islamic Fiqh, Law No. 1/1974